Knowledge, Anxiety, Depression, and Sleep Quality Among Medical Staff in Central South Areas of China During the Break of COVID-19: Does the Level of Hospitals Make a Difference? - Yang, Haojun; Shi, Ruiying; Chi, Yunfang; Qiao, Zhihua; Wu, Yuanxia; Zhu, Ziqing; Xiao, Bo; Feng, Li; Wang, Hongxing (Frontiers in Psychiatry, 2021)
Purpose: To evaluate the knowledge, anxiety, depression, and sleep quality toward COVID-19 among Chinese medical staff from tertiary and basic-level hospitals in central south areas of China. Method: A structured questionnaire was composed of Demographic and clinical characteristics of medical staff, Knowledge toward COVID-19 including epidemiology and clinical manifestations, The Self-rating anxiety scale (SAS), Center for Epidemiologic Studies Depression Scale (CES-D), and The Pittsburgh Sleep Quality Index (PSQI). It was administered to medical staff from tertiary hospitals (Group A) (n = 407) and basic-level hospitals (Group B) (n = 388) during February 2020 and May 2020. Results: Medical staff in group A had a stronger knowledge toward COVID-19 than group B (23.69±5.83 & 18.15±6.35, p < 0.001). Mild anxiety symptoms were found in both groups. The SAS scores (Mean±SD) of group B were 58.87±10.17, which was significantly higher than that of group A (52.59±12.09, p < 0.001). There were no significant differences in CES-D scores between the two groups (p = 0.981). The mean score of total PSQI in group B (8.41±3.03) was statistically higher than that of group A (7.31±3.74, p < 0.001). Additionally, the scores of sub-components of group B, including subjective sleep quality, sleep latency, sleep disorder, sleeping medication use and daytime dysfunction, were were significantly higher compared to Group A (p < 0.05). Conclusions: Our study showed greater anxiety, more severe depression and poorer sleep quality among medical staff in central south areas of China during the COVID-19 outbreak. Additionally, compared to the tertiary hospital group, medical staff from basic-level hospitals had poorer knowledge toward COVID-19 and worse mental health conditions. In addition, residence, specialty, title and education level may also be factors of knowledge of COVID-19 and psychiatry problems. In light of this information, more attention should be paid to early identification and intervention of symptoms of anxiety and depression in susceptible medical staff from the basic-level hospitals.